The Impact of Project Based Learning Model on Creative Thinking Ability of Forth Grade Students - Astuti, Nelly; Efendi, Ujang; Riswandi; Haya, Fadila Fagia (International Journal of Elementary Education, 2022)
Learning in schools still emphasizes basic level thinking skills. Learning still has not improved the higher-order thinking skills of students, and often uses teacher-centered learning. This causes the low creative thinking ability of students. This study aims to analyze the effect of project-based learning models on students' creative thinking skills. This research method is a quasi-experimental group design with a non-equivalent control group design used. The population is 50 people and the sample used is class IV A and IV B students, the sample is determined by non-probability sampling technique. Data were collected using pretest, posttest, and observation techniques. The results of this study are that there is a significant effect on project-based learning on the creative thinking skills of fourth grade elementary school students. Through the Project Based Learning model, students learn from their experiences and then apply them in everyday life. This learning model is expected to be able to improve students' creative thinking skills to construct their knowledge by being actively involved in complex learning processes.